High-strength corrosion-resisting steel and manufacturing method thereof

By designing the chemical composition and rolling control process of high-strength corrosion-resistant steel, the shortcomings of the existing medium and medium- and medium- and low-alloy high-strength corrosion-resistant steel materials in acid and alkali corrosion resistance are solved, and high strength, high toughness and low cost are achieved. Steel preparation, suitable for the manufacture of chemical liquid tank semi-trailer.

CN119194273AActive Publication Date: 2024-12-27МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411540494.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-27
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The prior art is difficult to provide low-alloy high-strength corrosion-resistant steel materials with excellent acid and alkali corrosion resistance and high plasticity at low cost, and cannot effectively replace stainless steel and aluminum alloys to meet the manufacturing needs of chemical liquid tank semi-trailers.

Method used

By designing the chemical composition system and rolling control process of high-strength corrosion-resistant steel, including a small amount of multi-composite design of Al-Cu-Cr-Ni-Sb-W, adopting LF+RH dual refining treatment and controlled rolling + segmented cooling + insulation The pit slow cooling process prepares high-strength corrosion-resistant steel with uniform, fine ferrite and pearlite structure.

Benefits of technology

It achieves high strength, high toughness and excellent corrosion resistance of strong acid and strong alkali, reduces the manufacturing cost of materials, and is suitable for the manufacturing of chemical liquid tank semi-trailer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194273A_ABST
    Figure CN119194273A_ABST
Patent Text Reader

Abstract

The invention provides high-strength corrosion-resisting steel and a manufacturing method of the high-strength corrosion-resisting steel, and provides the high-strength corrosion-resisting steel and the manufacturing method of the high-strength corrosion-resisting steel. 0.07 to 0.15% of Ni; 0.25 to 0.40 percent of Cu; 0.05% to 0.15% of W; 0.040 to 0.070 percent of Alt (aluminum nitride); 0.05 to 0.10 percent of Sb; 0.010 to 0.025 percent of Ti; the content of Nb is 0.020 to 0.040 percent; the content of Ca is 0.0010 to 0.0035 percent; 0.05 to 0.08 percent of C; 0.15 to 0.35 percent of Si; 0.50 to 0.70 percent of Mn; p < = 0.012%; s < = 0.002%; n < = 40 ppm; o is less than or equal to 30 ppm, and the balance is Fe and inevitable inclusions. Through the process design of controlled rolling, sectional cooling and heat preservation pit slow cooling, the product has high strength, high toughness and excellent strong acid and strong alkali corrosion resistance, and the cost is greatly reduced compared with stainless steel and aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel materials and production thereof, and in particular relates to a high-strength corrosion-resistant steel and a manufacturing method thereof. Background Art

[0002] Chemical raw materials such as strong acids and strong alkalis are extremely corrosive. When chemical liquid tank semi-trailers are used to transport strong acids and strong alkalis, the tank body is usually made of stainless steel or aluminum alloy. However, stainless steel and aluminum alloys are expensive, resulting in high manufacturing costs for chemical liquid tank semi-trailers. Low-alloy corrosion-resistant steel materials have excellent corrosion resistance, and their manufacturing costs are significantly lower than those of stainless steel and aluminum alloys, and are widely used. In order to improve the transportation efficiency of chemical liquid tank semi-trailers, a high-strength and thinned lightweight design is often adopted, but thinning makes the corrosion problem faced by the material more prominent. Therefore, it is necessary to develop low-alloy high-strength and corrosion-resistant steel materials with excellent acid and alkali corrosion resistance and high strength and plasticity to meet the requirements of low-cost manufacturing and high transportation efficiency of chemical liquid tank semi-trailers.

[0003] The Chinese patent with publication number CN109628842A published on April 16, 2019 discloses a corrosion-resistant steel for open coal transport cars with a yield strength of 550 MPa and a manufacturing method thereof, wherein the chemical composition is C: 0.049-0.072%, Si: 0.21-0.29%, Mn: 1.05-1.39%, P: ≤0.018%, S: ≤0.006%, Als: 0.015-0.045%, Cr: 0.45- 0.91%, Ni: 0.11-0.19%, Cu: 0.27-0.41, Nb: 0.018-0.039%, Ti: 0.015-0.035%, Sb: 0.046-0.099%, Sn: 0.034-0.079%, Mo: 0.11-0.19%, B: 0.0008-0.0019%, Ca: 0.0008-0.0030%; the rest is Fe and unavoidable impurities. eL ≥550MPa, R m ≥650MPa, A≥18%, -40℃ impact toughness ≥60J. Although the material has high strength, the elongation is insufficient. It has excellent corrosion resistance under the conditions of "room temperature, 20% H2SO4+3.5NaCl solution, soaking for 24h", and the corrosion rate is <4% relative to Q345B, but it is only suitable for dilute H2SO4 and Cl - environment.

[0004] The invention patent with the patent publication number CN 107868919A on April 3, 2018 discloses a hydrochloric acid and sulfuric acid corrosion resistant steel and a preparation method thereof, wherein the chemical composition is C: 0.02-0.04%, Si: 0.2-0.4%, Mn: 0.8-1.0%, P≤0.01%, S: 0.005-0.015%,

[0005] Cu: 0.25-0.35%, Cr: 0.3-0.4%, Ni: 0.1-0.2%, Sb: 0.05-0.15%, Sn: 0.05-0.15%, Mo: 0.05-0.15%. The yield strength of the material is ≥ 245MPa, the tensile strength is ≥ 400MPa, and the strength is relatively low. Under the conditions of "70℃, 50% H2SO4 solution, immersion for 24h", the corrosion rate is 55.1-60.2g / m 2 ·h (61.5-67.2mm / a), the corrosion rate of the material is faster in the concentrated sulfuric acid environment. Summary of the invention

[0006] The purpose of the present invention is to provide a high-strength corrosion-resistant steel and a method for manufacturing the same. Aiming at the complex corrosion environment in the tank body of a chemical liquid tank semi-trailer and the demand for lightweight development, a high-strength corrosion-resistant steel material is prepared from the perspective of chemical composition system design, steelmaking and controlled rolling process design. The steel material has excellent acid and alkali corrosion resistance and high strength and toughness, and can be used in the manufacture of chemical liquid tank semi-trailers to replace stainless steel and aluminum alloy.

[0007] The specific technical solutions of the present invention are as follows:

[0008] The present invention provides a high-strength corrosion-resistant steel, comprising the following chemical components in percentage by weight:

[0009] Cr: 1.3~2.0%; Ni: 0.07~0.15%; Cu: 0.25~0.40%; W: 0.05~0.15%; Alt: 0.040~0.070%; Sb: 0.05~0.10%; Ti: 0.010~0.025%; Nb: 0.020~0.040%; Ca: 0.0010~0.0035%; C: 0.05~0.08%; Si: 0.15~0.35%; Mn: 0.50~0.70%; P: ≤0.012%; S: ≤0.002%; N: ≤40ppm; O: ≤30ppm, the balance is Fe and unavoidable inclusions.

[0010] The high-strength corrosion-resistant steel has uniform and fine polygonal ferrite and pearlite structures; the average grain size of the ferrite is 5.6-7.0 μm, and the volume fraction of the ferrite is 90-95%.

[0011] The non-metallic inclusions in the high-strength corrosion-resistant steel have a diameter of 0.77 to 6.6 μm, an average diameter of 1.5 to 2.4 μm, and the number of non-metallic inclusions with a diameter less than 5 μm accounts for 96 to 98%;

[0012] The thickness of the high-strength corrosion-resistant steel is less than 10 mm;

[0013] The high-strength corrosion-resistant steel has high strength and high plasticity. eL ≥450MPa, R m ≥550MPa, A≥25%;

[0014] The high-strength corrosion-resistant steel has excellent low-temperature toughness: -60°C KV2≥120J (size is 10×10×55mm). The present invention adopts a small amount of Al-Cu-Cr-Ni-Sb-W multi-component composite design. Through the synergistic effect of the multi-alloys, the high-strength corrosion-resistant steel has excellent corrosion resistance: soaked in 40°C, 98% H2SO4 solution for 24 hours, the corrosion rate is 0.2-0.4mm / a; soaked in 70°C, 50% H2SO4 solution for 24 hours, the corrosion rate is 10-20mm / a; soaked in 40°C, 40% NaOH solution for 24 hours, the corrosion rate is 0.01-0.02mm / a.

[0015] The present invention provides a method for manufacturing high-strength corrosion-resistant steel, comprising the following process flow:

[0016] Hot metal pretreatment → converter smelting → refining → continuous casting → slab heating → controlled rolling → controlled cooling → coiling.

[0017] The refining adopts LF+RH double treatment, the total weak stirring time of LF furnace is ≥13min, which promotes the floating of non-metallic inclusions in molten steel, and the RH vacuum degassing time is ≥15min. Through the above rewards, the diameter of non-metallic inclusions is 0.77-6.6μm, the average diameter is 1.5-2.4μm, and the number of non-metallic inclusions with a diameter less than 5μm accounts for 96-98%.

[0018] In the continuous casting, the temperature of the molten steel casting ladle is controlled at 1530°C to 1550°C, the billet drawing speed is 1.1 to 1.4 m / min, the thickness of the continuous casting slab is 230 mm, and after the billet is cut, it is slowly cooled to below 100°C in the insulation pit, and the cooling rate is ≤15°C / h.

[0019] The slab heating process controls the temperature of the cast slab out of the furnace to 1180-1230°C and the furnace time to 160-220 minutes to promote the full solid solution of alloy elements, especially titanium carbonitride. The heating furnace adopts a weak reducing atmosphere with an excess air coefficient of 0.9-1.0 to reduce the oxidation and burning of Fe on the slab surface during the heating process.

[0020] After the steel billet leaves the heating furnace, it is descaled by high-pressure water before rolling.

[0021] The controlled rolling is carried out in two stages: rough rolling and finishing rolling. In the rough rolling stage, two four-roll reversible rolling mills are used for reciprocating rolling, with 3 and 5 passes respectively. The rolling temperature is controlled above 1050°C, and the cumulative reduction rate is ≥80%. Multiple large deformations are carried out at high temperatures to promote the recovery and recrystallization of deformed austenite grains and refine the austenite grain size. In the finishing rolling stage, 7 four-roll rolling mills are used for continuous rolling, the finishing rolling start temperature is ≤1030°C, and the cumulative deformation amount is ≥85%. Through cumulative large deformation, the deformation bands and dislocation density in the deformed austenite are increased, the deformation nuclei of the ferrite phase are increased, and the ferrite grains after phase transformation are refined. The finishing rolling final rolling temperature is controlled to be 840-890°C.

[0022] The controlled cooling adopts segmented cooling to control the coiling temperature within 50m of the tail of the hot-rolled coil to 640-660°C, the coiling temperature within 20m of the head of the hot-rolled coil to 650-680°C, and the coiling temperature in the middle of the hot-rolled coil to 590-630°C. After coiling, the steel coil is placed in a heat preservation pit and slowly cooled to ≤450°C, with a cooling rate of ≤0.2°C / min, and then taken out and air-cooled to room temperature to avoid the head and tail of the hot-rolled coil from cooling too fast, generating bainite structure, resulting in high strength and reduced plastic toughness at the head and tail of the hot-rolled coil.

[0023] The design ideas of the present invention are as follows:

[0024] C: C atoms have a small radius and can significantly improve the strength of the material by causing strong lattice distortion through interstitial solid solution. However, if the C content is too high, it will not only deteriorate the plasticity and welding properties of the steel, but also increase the crack sensitivity of the ingot. The present invention takes into account both the manufacturing cost and the toughness requirements and controls its content to 0.05-0.08%.

[0025] Si: Si is commonly used for deoxidation of molten steel and can also improve the strength of steel through solid solution strengthening. However, excessive Si content will produce iron oxide scale on the surface of the steel strip that is difficult to remove, deteriorating the surface quality of the steel. Therefore, the present invention controls the Si content to 0.15-0.35%.

[0026] Mn: Mn is one of the important deoxidizing elements in steel and can also improve strength through substitution solid solution strengthening. However, if the Mn content is too high, not only the stability of austenite is enhanced and bainite structure is easily generated, but also the manufacturing cost is increased and the welding performance is deteriorated. Therefore, the present invention controls the Mn content to 0.50-0.70%.

[0027] Alt: Al has a strong binding force with oxygen and is the most important deoxidizing element added during the smelting process of steel materials. Its deoxidizing ability is stronger than that of Si and Mn. It can also form a dense aluminum oxide film on the surface of steel to inhibit acid and alkali corrosion of the matrix. However, if the Al content is too high, the content of aluminum oxide inclusions in the steel will increase, which will deteriorate the toughness of the steel. Therefore, the present invention controls the Alt content to 0.040-0.070%.

[0028] Cr: Cr can promote the formation of α-FeOOH and replace part of the Fe in α-FeOOH. 3+ , forming nano-scale oxide α-FexCr1-xOOH, which effectively prevents SO4 2- At the same time, Cr also has a certain tendency to self-passivate in steel, which increases the electrode potential of the solid solution, so a higher content of Cr is used to improve acid resistance. However, if the Cr content is too high, it will significantly increase the hardenability of the material, easily generate bainite structure, and also deteriorate the welding performance. Therefore, the Cr content is controlled at 1.3-2.0%.

[0029] Ni: It can significantly improve the hydrochloric acid corrosion resistance and alkali corrosion resistance of the material, and can also form a high-temperature binary alloy with Cu to inhibit the occurrence of copper brittleness on the steel surface; however, Ni is a precious alloy and significantly increases the manufacturing cost of the material. Therefore, its content is controlled at 0.07-0.15%.

[0030] Cu: reacts with Sb to form Cu2Sb, inhibits cathode reaction, and improves acid corrosion resistance; Cu can also react with hydroxide particles to form a dense passivation layer on the surface of steel, thereby improving alkali corrosion resistance. However, Cu has a low melting point of only 1073°C, and a high content will produce copper brittle defects on the surface of hot-rolled coils. Therefore, the Cu content is controlled at 0.25-0.40%.

[0031] Sb: Sb is one of the key elements to improve the acid corrosion resistance of steel. It is enriched on the steel surface in an acidic environment to form a dense rust layer of Sb2O3 and Sb2O5, which blocks the corrosion of the substrate by the corrosive medium. As the antimony content increases, the improvement of the acid corrosion resistance weakens, and Sb is a low melting point alloy element. Too high a content increases the crack sensitivity of the slab. Therefore, the present invention controls the Sb content to 0.05-0.10%.

[0032] W: inhibits anodic reaction and reduces local corrosion of steel. Adding W together with Ni can significantly improve the acid and alkali corrosion resistance of steel. However, W has a high cost and significantly improves the hardenability of the material, making it easy to generate bainite structure. Therefore, its content is controlled at 0.05-0.15%.

[0033] Ti: Ti is a strong nitride-forming element with a high solid solution temperature. It inhibits the growth of austenite grains in the heat-affected zone during welding and improves the low-temperature toughness of the heat-affected zone. The bonding force between Ti and C is much greater than that between Cr and C, which reduces the content of Cr carbides, eliminates the depletion of Cr at the grain boundary, and improves the resistance to intergranular corrosion. However, if the titanium content is too high, large particles of titanium nitride inclusions are easily precipitated, reducing the low-temperature toughness of the material. Therefore, the Ti content is controlled at 0.010% to 0.025%.

[0034] Nb: Nb has strong grain refinement and precipitation strengthening effects. In the high temperature stage, niobium carbonitride is precipitated to pin dislocations, inhibit the recovery and recrystallization of deformed austenite, increase dislocation density, improve nucleation rate, and refine grains; in the low temperature stage, niobium carbide two-phase particles are precipitated to improve material strength. However, the alloy price of Nb is relatively high, which significantly increases the material manufacturing cost. Therefore, the Nb content is controlled at 0.020% to 0.040%.

[0035] Ca: Ca promotes the spheroidization of non-metallic inclusions and improves the low-temperature toughness and corrosion resistance of the material. The Ca content is controlled at 0.0010% to 0.0035%.

[0036] P: P is a common residual element in steel, which is easily enriched at the grain boundary and reduces the low-temperature toughness of the material. However, controlling the P content to an extremely low level will increase the smelting cost. Therefore, the present invention controls its content to ≤0.012%.

[0037] S: Although S can form a dense Cu2S passivation film with Cu to improve corrosion resistance, S is easy to form MnS inclusions with Mn, which deteriorates the plasticity and toughness of steel, especially with the increase of strength, the impact on the plasticity and toughness of steel is more significant; and S is easy to react with Ti at high temperature to precipitate coarse Ti4C2S2 two-phase particles, weakening the effect of micro-alloying element Ti. Therefore, the present invention regards S as a harmful element and controls its content to ≤0.002%.

[0038] N, O: N and O are residual harmful gas elements in steel. If the N content is too high, it is easy to combine with Ti to precipitate coarse TiN particles at high temperature, reducing the toughness of the material; O forms oxide inclusions in the steel, reducing the toughness and corrosion resistance of the material. Therefore, the present invention controls N≤0.0040% and O≤0.0030%.

[0039] Compared with the prior art, the present invention aims at the strong acid and strong alkali corrosive media in the tank body of the chemical liquid tank semi-trailer, and improves the acid and alkali corrosion resistance of the material through a small amount of multi-element interaction of Al-Cu-Cr-Ni-Sb-W; and adopts single Ti micro-alloying to improve the strength of the material. LF+RH double refining treatment is adopted to reduce the content of gas and non-metallic inclusions and improve the cleanliness of molten steel. Trace Ca is added to promote the spheroidization of non-metallic inclusions; reduce the corrosion induced by non-metallic inclusions as pitting sources, and improve the toughness of the material. In view of the characteristics of high-strength corrosion-resistant steel containing alloy elements such as Cu, Cr, Ni, and W, strong hardenability, and narrow hot rolling process control window, a uniform and fine ferrite + pearlite structure is obtained through the design of controlled rolling + segmented cooling + slow cooling in an insulation pit. The steel plate provided by the present invention has high strength, high toughness and excellent strong acid and alkali corrosion resistance, and the cost is greatly reduced compared with stainless steel and aluminum alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The microstructure morphology of Example 2 of the present invention under an optical microscope shows a uniform and fine ferrite+pearlite structure, with an average ferrite grain size of 6.1 μm and a ferrite volume fraction of 92%. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1-Example 4

[0043] A high-strength corrosion-resistant steel comprises the following chemical components in mass percentage: as shown in Table 1, the remainder not shown in Table 1 is Fe and unavoidable impurities.

[0044] Comparative Example 1-Comparative Example 4

[0045] A high-strength corrosion-resistant steel comprises the following chemical components in mass percentage: as shown in Table 1, the remainder not shown in Table 1 is Fe and unavoidable impurities.

[0046] Table 1 Chemical compositions of the embodiments of the present invention and comparative examples (O and N are in ppm, the rest are in wt%)

[0047]

[0048] The production methods of the above embodiments and comparative examples include the following process flow: molten iron pretreatment → converter smelting → refining → continuous casting → slab heating → controlled rolling → controlled cooling → coiling.

[0049] Molten steel is smelted according to the above chemical composition, and LF+RH double treatment is used for refining. The total weak stirring time of LF furnace is ≥13min to promote the floating of non-metallic inclusions in molten steel, and the RH vacuum degassing time is ≥15min. The temperature of the molten steel casting ladle is controlled at 1530℃~1550℃, the billet drawing speed is 1.1~1.4m / min, the thickness of the continuous casting slab is 230mm, and the billet is slowly cooled to below 100℃ in the insulation pit after cutting, and the cooling rate is ≤15℃ / h.

[0050] In the slab heating process, the temperature of the cast billet out of the furnace is controlled at 1180-1230℃, the furnace time is 160-220min, the heating furnace adopts a weak reducing atmosphere, and the air excess coefficient is 0.9-1.0. After the billet leaves the heating furnace, it is descaled by high-pressure water and then rolled. The rolling is carried out in two stages: rough rolling and finishing rolling. The rolling temperature in the rough rolling stage is controlled at above 1050℃, and the cumulative reduction rate is ≥80%. In the finishing rolling stage, a 7-stand four-roll rolling mill is used for continuous rolling, the finishing rolling start temperature is ≤1030℃, the cumulative deformation is ≥85%, and the finishing rolling final rolling temperature is 840-890℃. After finishing rolling, segmented cooling is adopted to control the coiling temperature within 50m of the tail of the hot-rolled coil to 640-660℃, the coiling temperature within 20m of the head to 650-680℃, and the coiling temperature in the middle of the hot-rolled coil to 590-630℃. The steel coil is then placed in an insulation pit and slowly cooled to ≤450℃, with a cooling rate of ≤0.2℃ / min, and then taken out and air-cooled to room temperature.

[0051] The main process parameters of the smelting and rolling steps of the embodiments and comparative examples are shown in Table 2.

[0052] Table 2 Main process parameters of smelting and rolling process of embodiment and comparative example

[0053]

[0054] Tensile tests and impact tests were carried out in accordance with GB / T 228.1 "Metallic materials tensile test Part 1: Room temperature test method" and GB / T229 "Metallic materials Charpy pendulum impact test method", and non-metallic inclusions were detected using an ASPEX inclusion analyzer. The mechanical properties, low-temperature toughness and non-metallic inclusions of the embodiments and comparative examples are shown in Table 3.

[0055] Table 3 Mechanical properties, toughness, non-metallic inclusions of examples and comparative examples

[0056]

[0057]

[0058] The corrosion test was carried out according to JB / T 7901 "Metallic Materials Laboratory Uniform Corrosion Full Immersion Test Method", the test period was 24 hours, the sample size was 25mm×50mm×3.5mm, and the sample surface was processed by a grinder. The corrosion resistance of the embodiment and the comparative example in strong acid and strong alkali environments is shown in Table 4.

[0059] Table 4 Corrosion resistance of embodiments and comparative examples

[0060]

[0061] Comparative Example 1 does not add W and Sb elements, so the material has insufficient resistance to strong acid and strong alkali corrosion;

[0062] Comparative Example 2 Due to the insufficient content of Al, Cr, Ni, and Cu elements, the material's ability to resist strong acid and strong alkali corrosion is reduced;

[0063] In Comparative Example 3, due to the high content of C, Mn, P, and S, and the short LF and RH refining treatment time, the material has a high content of large-sized non-metallic inclusions, high material strength, and reduced low-temperature toughness and corrosion resistance.

[0064] Although the composition of Comparative Example 4 meets the requirements of the present invention, due to the low finishing reduction rate, the dislocation density in the deformed austenite grains before the phase transformation is reduced, the ferrite nucleation rate is reduced, and the coiling temperature in the middle of the hot-rolled coil is relatively high, which makes the ferrite grains coarsened, the material strength is reduced, and the low-temperature toughness is insufficient.

[0065] In summary, the high-strength corrosion-resistant steel plate obtained according to the chemical composition and controlled rolling and controlled cooling process control technology of the present invention has a yield strength ≥450MP, a tensile strength ≥550MPa, an elongation ≥25%, and -60℃ KV2 ≥120J. It has excellent acid and alkali corrosion resistance and can be used in the manufacture of chemical liquid tank trailers.

[0066] The underlined data above do not meet the requirements of the present invention.

[0067] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A high-strength corrosion-resistant steel, characterized in that: The high-strength corrosion-resistant steel includes the following chemical compositions by mass percentage: Cr:1.3~2.0%; Ni: 0.07~0.15%; Cu: 0.25~0.40%; W: 0.05~0.15%; Alt: 0.040~0.070%; Sb: 0.05~0.10%; Ti: 0.010~0.025%; Nb: 0.020~0.040%; Ca: 0.0010~0.0035%; C: 0.05~0.08%; Si: 0.15~0.35%; Mn: 0.50~0.70%; P :≤0.012%; S: ≤0.002%; N: ≤40ppm; O: ≤30ppm, the balance is Fe and unavoidable inclusions.

2. The high-strength corrosion-resistant steel according to claim 1, characterized in that: The high-strength corrosion-resistant steel microstructure consists of polygonal ferrite and pearlite, wherein the average grain size of ferrite is 5.6-7.0 μm, and the volume fraction of ferrite is 90-95%; the diameter of non-metallic inclusions is 0.77-6.6 μm, and the average diameter is 1.5-2.4 μm, wherein the number of non-metallic inclusions with a diameter less than 5 μm accounts for 96-98%.

3. The high-strength corrosion-resistant steel according to claim 1, characterized in that: The R of the high strength corrosion resistant steel eL ≥450MPa, R m ≥550MPa, A≥25%; Low temperature toughness: -60℃KV2≥120J; Immersed in 98% H2SO4 solution at 40℃ for 24h, the corrosion rate is 0.2~0.4mm / a; Immersed in 50% H2SO4 solution at 70℃ for 24h, the corrosion rate is 10~20mm / a; Immersed in 40% NaOH solution at 40℃ for 24h, the corrosion rate is 0.01~0.02mm / a.

4. A method for manufacturing the high-strength corrosion-resistant steel according to any one of claims 1 to 3, characterized in that: The manufacturing method comprises the following process flow: Hot metal pretreatment → converter smelting → refining → continuous casting → slab heating → controlled rolling → controlled cooling → coiling.

5. The manufacturing method according to claim 4, characterized in that: The refining adopts LF+RH double treatment, the total weak stirring time of the LF furnace is ≥13min, which promotes the floating of non-metallic inclusions in the molten steel, and the RH vacuum degassing time is ≥15min.

6. The manufacturing method according to claim 4, characterized in that: In the continuous casting, the temperature of the molten steel casting ladle is controlled at 1530° C. to 1550° C., the billet drawing speed is 1.1 to 1.4 m / min, and after the billet is cut, it is slowly cooled to below 100° C. in the insulation pit, and the cooling rate is ≤15° C. / h.

7. The manufacturing method according to claim 4, characterized in that: The slab heating process controls the temperature of the cast slab out of the furnace to be 1180-1230° C. and the time in the furnace to be 160-220 min.

8. The manufacturing method according to claim 4, characterized in that: The controlled rolling is carried out in two stages: rough rolling and finishing rolling. The rolling temperature in the rough rolling stage is controlled to be above 1050°C, and the cumulative reduction rate is ≥80%. The finishing rolling stage adopts a 7-stand four-roller rolling mill, the finishing rolling start temperature is ≤1030°C, the cumulative deformation is ≥85%, and the finishing rolling final temperature is controlled to be 840-890°C.

9. The manufacturing method according to claim 4, characterized in that: The controlled cooling adopts segmented cooling to control the coiling temperature within 50m of the tail of the hot-rolled coil to 640-660°C, the coiling temperature within 20m of the head of the hot-rolled coil to 650-680°C, and the coiling temperature in the middle of the hot-rolled coil to 590-630°C. Then the steel coil is placed in a heat preservation pit for slow cooling to ≤450°C, with a cooling rate of ≤0.2°C / min, and then taken out for air cooling to room temperature.

Citation Information

Patent Citations

  • Steel plate resistant to sulfuric acid dew point corrosion and manufacturing method for steel plate

    CN104357754A

  • Steel for acid soil corrosion resistant buried structure, and manufacturing method thereof

    CN109082594A

  • High-strength fire-resistant corrosion-resistant building steel and manufacturing method thereof

    CN110343957A

  • Hot-rolled double-phase high-corrosion-resistance steel plate with tensile strength of 650 MPa and manufacturing method thereof

    CN115261723A

  • Economical marine atmosphere corrosion resistant steel and production method thereof

    CN115747637A